Are you somebody : the accidental memoir of a Dublin woman - O'Faolain, Nuala (New York, NY Henry Holt, 1998)
Born one of nine children into a penniless North Dublin family, Nuala O'Faolain was saved from a harrowing childhood by her love of books and reading. Pushing constantly at the boundaries of Ireland's confining Catholic culture, she ultimately become one of the country's best-known columnists. But as she entered middle age alone and dressed, her professional success did little to ease her longing for a deep connection to the world. In this extraordinary memoir, O'Faolain has distilled her experiences into a wisdom that can only come from an obstinate refusal to shrink from life. The story of how she defines herself outside the traditional roles assigned to women provides an exhilarating example of courage, honesty, and bold living
D., 3/01
Keywords: O'Faolain, Nuala -- Biography; Women journalists -- Biography -- Ireland